The Effect of Solution Heat Treatment Time on the Phase Formation and Selected Mechanical Properties of Ti-25Ta-xZr Alloys for Application as Biomaterials - Kuroda, Pedro Akira Bazaglia [UNESP]; Quadros, Fernanda de Freitas [UNESP]; Afonso, Conrado Ramos Moreira; Grandini, Carlos Roberto [UNESP] (Springer Nature, 2021)
This study analyzed the influence of solution heat treatment on the structure, microstructure, hardness, and elastic modulus of a ternary alloys Ti-25Ta-xZr system, where the zirconium content was varied to 0, 10, 20, 30, and 40 wt%. The solution heat treatments (SHT) performed in this paper were conducted at 1273 K during 0, 3, and 6 h. Structural and microstructural analyses were performed using x-ray diffraction, optical microscopy, and scanning, and transmission electron microscopy. An analysis of the alloys’ selected mechanical properties was carried out using microhardness and dynamic elastic modulus measurements. The results showed that zirconium helped stabilize the β phase since by adding zirconium to the alloy, the tantalum volumetric fraction increased. SHT with longer duration induced precipitation of the β phase in the Ti-25Ta-Zr alloy system. With higher zirconium concentrations, Ti-25Ta-xZr alloys showed better mechanical compatibility with human bone with a low elastic modulus but higher hardness values, making the mechanical conformation of the alloy more difficult. The Ti-25Ta-30Zr alloy had high hardness and elastic modulus after being subjected to solution for 3 and 6 h, indicating ω phase precipitation, and Ti-25Ta-40Zr alloy showed the lowest value of elastic modulus of 57 GPa with good prospects for applications as a metallic biomaterial.
Keywords: mechanical properties; metallic biomaterial; solution heat treatment; Ti alloys